The effect of the civil war on Rwanda's bean seed systems and unusual bean diversity - Sperling, L. (Springer, 2001)
The Rwandan civil war escalated in 1994, killing 800 000 people and displacing another 2 million. Agriculture, the occupation of over 90% of the Rwandans was acutely affected as violence peaked in the middle of the growing season. This article analyses the effects of the war on bean varietal diversity as, pre-war, Rwandan farmers grew the greatest range of varieties in active use anywhere and maintaining such diversity was central to sustainable production. Extensive pre- and post-war assessments show the current bean varietal situation to be relatively promising. The war had lesser effects than anticipated: fighting was staggered, harvests were better than expected, and local seed channels generally continued functioning. However, changes in varietal profiles were noted over the longer term due to two trends: farmers' needs to intensify production and to respond to swift and widespread root rot pressures. The article ends with five methodological reflections on how to assess varietal erosion in sites of acute disruption.